Examen Especial a Ingresos y Gastos de la Compañía de Transporte Escolar “Entre Ríos” S.A., Periodo 01 de Enero-31 de Diciembre 2022. - Condoy García, María de los Angeles (2024)
The following work of curricular integration consists of the application of a Special Examination to Revenues and Expenses of the School Transportation Company "Entre Ríos" S.A., Period January 01 - December 31, 2022, for the purpose of evaluating the level of efficiency and effectiveness of the company's internal control system implemented for items of income and expenses, in order to accomplish the following objectives: to determine the reasonableness of the balances of the items of income and expenses presented in the financial statements, through audit procedures, to establish possible errors and inconsistencies and to issue the special examination report containing comments, conclusions and recommendations on the results obtained to identify areas for improvement. For the development of the special examination, audit phases were applied. First, a preliminary and specific plan was developed based on the findings of the previous visit to the company and a review of the internal control system was conducted; in the second phase, audit programs were designed, where the findings of the deficiencies found were obtained; in the third phase, the communication of results was conducted resulting in the preparation of an audit report, containing comments, conclusions, and recommendations. In the aftermath of the special examination, it was determined that the income and expense items reflected in the financial statements of the company demonstrate reasonable balances, except for the item General Expenses, which is included in the Management Expenses account due to the absence of corresponding documentation on some of the sales vouchers, which are not reviewed by the Supervisory Board.; Due to this weakness, the sales vouchers should be taxed in accordance with the applicable tax regulations.